2010
DOI: 10.3945/ajcn.2010.29876
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and tea intake and risk of brain tumors in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort study

Abstract: Background: In a recent US cohort study, total coffee and tea consumption was inversely associated with risk of glioma, and experimental studies showed that caffeine can slow the invasive growth of glioblastoma. Objective: The objective was to examine the relation between coffee and tea intake and the risk of glioma and meningioma in a large European cohort study, the European Prospective Investigation into Cancer and Nutrition (EPIC). Design: Data on coffee and tea intake were collected from men and women rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 17 publications
2
39
1
Order By: Relevance
“…A manual search of the references of the included studies did not yield any new eligible studies. Among the studies included, 20 were from the USA or Canada (Heilbrun et al, 1986;Kinlen et al, 1988;Shibata et al, 1994;Zheng et al, 1996;Harnack et al, 1997;Michaud et al, 1999Michaud et al, , 2001Su and Arab, 2002;Adebamowo et al, 2005;Michels et al, 2005;Silvera et al, 2007;Ganmaa et al, 2008;Tworoger et al, 2008;Boggs et al, 2010;Holick et al, 2010;Ren et al, 2010;Dubrow et al, 2012;Sinha et al, 2012;Hildebrand et al, 2013), 15 were from Europe (Goldbohm et al, 1996;Hartman et al, 1998;Terry and Wolk, 2001;Zeegers et al, 2001;Larsson and Wolk, 2005;Hirvonen et al, 2006;Steevens et al, 2007;Larsson et al, 2009;Bhoo Pathy et al, 2010;Michaud et al, 2010;Fagherazzi et al, 2011;Ros et al, 2011;Braem et al, 2012;Shafique et al, 2012;Geybels et al, 2013) and 22 were from Asia (Key et al, 1999;Nagano et al, 2001;Tsubono et al, 2001;Hoshiyama et al, 2002;Allen et al, 2004;…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A manual search of the references of the included studies did not yield any new eligible studies. Among the studies included, 20 were from the USA or Canada (Heilbrun et al, 1986;Kinlen et al, 1988;Shibata et al, 1994;Zheng et al, 1996;Harnack et al, 1997;Michaud et al, 1999Michaud et al, , 2001Su and Arab, 2002;Adebamowo et al, 2005;Michels et al, 2005;Silvera et al, 2007;Ganmaa et al, 2008;Tworoger et al, 2008;Boggs et al, 2010;Holick et al, 2010;Ren et al, 2010;Dubrow et al, 2012;Sinha et al, 2012;Hildebrand et al, 2013), 15 were from Europe (Goldbohm et al, 1996;Hartman et al, 1998;Terry and Wolk, 2001;Zeegers et al, 2001;Larsson and Wolk, 2005;Hirvonen et al, 2006;Steevens et al, 2007;Larsson et al, 2009;Bhoo Pathy et al, 2010;Michaud et al, 2010;Fagherazzi et al, 2011;Ros et al, 2011;Braem et al, 2012;Shafique et al, 2012;Geybels et al, 2013) and 22 were from Asia (Key et al, 1999;Nagano et al, 2001;Tsubono et al, 2001;Hoshiyama et al, 2002;Allen et al, 2004;…”
Section: Resultsmentioning
confidence: 99%
“…Of the 547 citations identified from database searches, 87 datasets from 57 articles (Heilbrun et al, 1986;Kinlen et al, 1988;Shibata et al, 1994;Goldbohm et al, 1996;Zheng et al, 1996;Harnack et al, 1997;Hartman et al, 1998;Key et al, 1999;Michaud et al, 1999Michaud et al, , 2001Michaud et al, , 2010Nagano et al, 2001;Terry and Wolk, 2001;Tsubono et al, 2001;Zeegers et al, 2001;Hoshiyama et al, 2002;Su and Arab, 2002;Allen et al, 2004;Suzuki et al, 2004Suzuki et al, , 2005Suzuki et al, , 2009Adebamowo et al, 2005;Michels et al, 2005;Larsson and Wolk, 2005;Hirvonen et al, 2006;Kikuchi et al, 2006;Kuriyama et al, 2006;Ide et al, 2007;Lee et al, 2007;Silvera et al, 2007;Steevens et al, 2007;Sun et al, 2007;Ganmaa et al, 2008;Kurahashi et al, 2008Kurahashi et al, , 2009Li et al, 2008;Lin et al, 2008;Tworoger et al, 2008;Inoue et al, 2009;Larsson et al, 2009;Ui et al, Iwasaki et al,...…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies have shown that high coffee and tea intake are inversely correlated with glioma risk (64,65). The first one reflects data from three independent cohort studies.…”
Section: Lifestyle Factorsmentioning
confidence: 98%
“…Adults in the United States and many European countries typically drink 2 to 3 cups of coffee a day12. With economic development coffee consumption is becoming more common in Asia including South Korea, China and India.…”
mentioning
confidence: 99%